2011
DOI: 10.1111/j.2042-7158.2010.01160.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lovastatin on the pharmacokinetics of diltiazem and its main metabolite, desacetyldiltiazem, in rats: possible role of cytochrome P450 3A4 and P-glycoprotein inhibition by lovastatin

Abstract: It might be considered that lovastatin resulted in reducing the first-pass metabolism in the intestine and/or in the liver via inhibition of CYP3A4 and increasing the absorption of diltiazem in the intestine via inhibition of P-gp by lovastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The transport of Gpz from mucosal to serosal side was increased in the presence of Lov and verapamil (standard P-gp inhibitor). Lov is a P-gp substrate [22] and it also a potent inhibitor of P-gp [23][24][25]. Results were shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The transport of Gpz from mucosal to serosal side was increased in the presence of Lov and verapamil (standard P-gp inhibitor). Lov is a P-gp substrate [22] and it also a potent inhibitor of P-gp [23][24][25]. Results were shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Besides, Martirosyan et al found that lovastatin had a synergistic effect with doxorubicin in a dose-dependent manner in ovarian cancer cells treatment through P-gp inhibition increasing doxorubicin systemic exposure [49]. Moreover, co-administration of lovastatin increased AUC 0-∞ and C max of diltiazem and nicardipine by the inhibition of CYP3A4 and P-gp in rats and mice [50,51]. Recently, Sanneboina et al demonstrated that lovastatin increased plasma concentration of glipizide and repaglinide by lovastatin inhibition effect of both P-gp and CYP3A4 in rats and rabbits [52].…”
Section: Discussionmentioning
confidence: 99%
“…Grapefruit juice, if consumed in large amounts, may also significantly increase the inhibitory activity of lovastatin on HMG-CoA reductase 15. Furthermore, there is clear evidence that lovastatin inhibits the membrane transport protein P-glycoprotein, which plays an important role in the detoxification of drugs 1,17,18…”
Section: Pharmacological Effects and Interactions Of Red Yeast Ricementioning
confidence: 99%
“…This efflux transporter, which is predominantly found in excretory tissues, actively transports not only endogenous substances, such as steroids and cytokines, but also potentially toxic xenobiotics out of cells. Thus, the inhibitory effect of monacolin K (lovastatin) on this transporter can also significantly influence the bioavailability and the distribution of drugs 17,18…”
Section: Pharmacological Effects and Interactions Of Red Yeast Ricementioning
confidence: 99%